A Cooperação Bilateral Brasil-Moçambique, com Enfoque Especial na Área da Defesa - Luca Bussotti; Ernesto Macamo (Cadernos de Estudos Africanos)
This article aims at understanding the evolution of bilateral relationships Brazil-Mozambique, especially in the field of defence. The relationships between these two countries entered a new phase with the advent of Lula and, from the Mozambican side, of Guebuza. These relationships had as their focus sectors health and education, but also in the area of defence many advances were registered. The research, based on a qualitative methodology, concludes that the bilateral relationships in the field of defence were characterized by an “ambiguous convergence”, in which Brazil was committed to support programs of development, but at the same time trained Mozambican soldiers and sold equipment which Mozambican government used to reopen a front of war against Renamo.